Language regimes in transformation : future prospects for German and Japanese in science, economy, and politics - Coulmas, Florian (Contributions to the sociology of language, 2007)
Globalization has many faces. One of them is the transformation of language regimes. This book provides an in-depth account of how two second-tier languages, Japanese and German, are affected by this process. In the international arena, they no longer com.